(3GdeLehY GdePgH aj bhGYO GdePgHs - (3UdGM GdOjf Ndjd Hf cjcdOi GdYdGFi GdTGaYj,J (B761 (3g` s
(3ChdgG (B:s
(3GdMeO ddg aGJM GHhGH GdeYGQa dWGdHgG CeG HYO aEf GdYde CTQa GdeWGdH hGYdGgG Yf CHj gQjQI QVi Gddg Cf QShd Gddg Udi Gddg Ydjg hSde bGd (B( (3EPG eGJ GdEfSGf Efg EfbWY Yedg EdG ef KdGK UObI LGQjI Ch Ydi jfJaY Hg Ch hdO UGdM jOYhG dg s
(3BNQgG (B:s
(3hai GdeSFdI eHGMK cKjQI djS gPg ehVY PcQgG hbO CaQOgG HeUfa eSJbd hgPG BNQ eG jSQg Gddg JYGdi s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3YdjgG JhbjY eMeO Hf GdTMfI hZjQges
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3CUhd Gdabgs